Cerebral Alterations Following Experimental Multiple Trauma and Hemorrhagic Shock. Issue 2 (February 2018) - Vogt, Nina; Herden, Christiane; Roeb, Elke; Roderfeld, Martin; Eschbach, Daphne; Steinfeldt, Thorsten; Wulf, Hinnerk; Ruchholtz, Steffen; Uhl, Eberhard; Schöller, Karsten
Abstract : ABSTRACT: Multiple trauma (MT) associated with hemorrhagic shock (HS) might lead to cerebral hypoperfusion and brain damage. We investigated cerebral alterations using a new porcine MT/HS model without traumatic brain injury (TBI) and assessed the neuroprotective properties of mild therapeutic hypothermia. Male pigs underwent standardized MT with HS (45% or 50% loss of blood volume) and resuscitation after 90/120 min (T90/T120). In additional groups (TH90/TH120) mild hypothermia (33°C) was induced following resuscitation. Normothermic or hypothermic sham animals served as controls. Intracranial pressure, cerebral perfusion pressure (CPP), and cerebral oxygenation (Pti O2 ) were recorded up to 48.5 h. Serum protein S-100B and neuron-specific enolase (NSE) were measured by ELISA. Cerebral inflammation was quantified on hematoxylin and eosin -stained brain slices; Iba1, S100, and inducible nitric oxide synthase (iNOS) expression was assessed using immunohistochemistry. Directly after MT/HS, CPP and Pti O2 were significantly lower in T90/T120 groups compared with sham. After resuscitation both parameters showed a gradual recovery. Serum protein S-100B and NSE increased temporarily as a result of MT/HS in T90 and T90/T120 groups, respectively. Cerebral inflammation was found in all groups. Iba1-staining showed significant microgliosis in T90 and T120 animals. iNOS-staining indicated a M1 polarization. Mild hypothermia reduced cerebral inflammation in the TH90 group, but resulted in increased iNOS activation. In this porcine long-term model, we did not find evidence of gross cerebral damage when resuscitation was initiated within 120 min after MT/HS without TBI. However, trauma-related microglia activation and M1 microglia polarization might be a consequence of temporary hypoxia/ischemia and further research is warranted to detail underlying mechanisms. Interestingly, mild hypothermia did not exhibit neuroprotective properties when initiated in a delayed fashion.